Análise das eficiências energética e econômica da produção de leite bovino em explorações familiares na região de Botucatu, estado de São Paulo - Costa, Zoraide da Fonseca [UNESP]; Bueno, Osmar de Carvalho [UNESP] (My University, 2010)
This study aimed to analyze the energy and economic efficiency rate of family farms producing milk in the city of Pardinho, Sao Paulo state. The hypothesis that guides the study is that energy expenditure may be coincident with economic expenditure, showing that there is a relationship between these flows, which can be sustainable or not. To better define the producers studied, we adopted the criteria outlined by the Brazilian agricultural credit system (FEAP). Through primary data obtained through oral accounts, the technical itineraries were reconstituted detailing the operations employed. Four producers were found to have different technical itineraries. Producer One presented the highest efficiency rates, 8.66 (energy) and 1.48 (economic). It was possible to observe that the efficiencies coincide and that, when related, they provide a broader idea of energy resource allocation and, thus, a better view of the agroecosystem sustainability.

O objetivo deste trabalho foi analisar os índices de eficiência energética/econômica das explorações agropecuárias familiares produtoras de leite no município de Pardinho, Estado de São Paulo. Para melhor definição dos produtores familiares estudados foram utilizados os critérios do sistema oficial de crédito rural FEAP. Por intermédio de dados primários, obtidos por relatos orais, foram reconstituídos os itinerários técnicos detalhando as operações utilizadas. Foram encontrados quatro produtores com diferentes itinerários técnicos. Os produtores 1 e 2 foram os que obtiveram um maior índice de eficiência. As fontes de energia não renováveis na forma de fertilizantes químicos foram as que apresentaram maior participação, uma média de 82,9% para os dispêndios energéticos e 52,86% para os econômicos. Ao relacionar as eficiências pode-se verificar que as duas formas de análises são próximas e quando relacionadas há uma ideia mais ampla da alocação dos recursos energéticos e, com isso, uma melhor visão da sustentabilidade do agroecossistema.
Analysis of economic and energy efficiency of dairy cattle production in family farms in the region of Botucatu, Sao Paulo state
Keywords: Family agriculture; Dairy cattle; Sustainability; Brazil; Agricultura familiar; Bovinocultura de leite; Sustentabilidade